Effect of Socioeconomic Inequality on Overweight and Obesity in Children: A Review of Systematic Reviews - Fatemeh Mehravar (Journal of Clinical and Basic Research, 2019)
Background and objectives: Obesity has become a global epidemic. Previous studies have reported a relationship between obesity in adults and socioeconomic factors, but the results regarding such relationship in the case of childhood obesity have been inconsistent. Therefore, this study aimed to determine the relationship between socioeconomic inequalities and overweight/obesity in children. Methods: All meta-analysis, systematic and descriptive or correlational reviews on obesity in children and adolescents that have been published in English between January 2001 and January 2019 were included in the study. We performed the search for articles in the following databases: MEDLINE, Embase, Web of Science, Cochrane Library and Google Scholar. Each review article was subjected to qualitative evaluation using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool. Results: Of 46 articles that met the inclusion criteria, five systematic reviews were included after carefully reading the abstract and the full text of the articles. The prevalence of overweight and obesity in children differed in different socioeconomic groups. Ethnicity was a confounding factor that could change this relationship. Conclusion: Strong evidence supports the relationship between socioeconomic status and overweight or obesity in children. Therefore, it is recommended to consider the socioeconomic status when planning for control and prevention of childhood obesity.